Chelation and Stereodirecting Group Effects on Regio- and Diastereoselective Samarium(II)-Water Allylic Benzoate Reductions - Stockdale, Trevor F.; Leitch, Michael A.; O’Neil, Gregory W. (Synthesis, 2020)
SmI2(H2O)n reductions of allylic benzoates adjacent to a trisubstituted alkene occur in high yields with complete regioselectivity and good diastereoselectivity (up to 90:10) for substrates containing properly positioned stereodirecting- and chelating groups. The outcome of these reactions can be rationalized by ring conformation considerations of a proposed chelated organosamarium intermediate, and a mechanism involving intramolecular protonation by a samarium-bound water.
Keywords: samarium; reduction; diastereoselective; regioselective; chelation